KARAKTERISTIK AKAR RENGAS (GLUTA RENGHAS L.) DI DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR RIAU - Indriani, Vema Dewi; Wan Syafi’i; Yustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Buluh Cina Village is a riparian area in the Kampar River Basin with diverse habitat conditions, ranging from permanently flooded areas and periodically flooded areas to non-flooded areas. These environmental conditions are assumed to influence the root characteristics of rengas (Gluta renghas L.), a plant species commonly found in riparian and freshwater swamp habitats. This study aimed to determine the morphological and anatomical characteristics of rengas roots (Gluta renghas L.) in Buluh Cina Village, Siak Hulu District, Kampar Regency, Riau. This research used a mixed methods approach with a naturalistic perspective and descriptive survey method. Data were collected through direct observation and documentation at three research stations, namely Station I as a permanently flooded area, Station II as a periodically flooded area, and Station III as a non-flooded area. The observed parameters included root length, root diameter, root color, number of lateral roots, presence of adventitious roots, and root anatomical structures consisting of the epidermis, cortex, aerenchyma, xylem, and phloem. The results showed differences in rengas root characteristics among the three stations. Morphologically, Station I was characterized by a larger main root diameter, horizontally spreading lateral roots, and the presence of adventitious roots. Station II showed transitional characteristics, while Station III had longer main roots with shorter and more concentrated lateral roots. Anatomically, Station I showed a thicker cortex and the clearest aerenchyma development, Station II had fewer aerenchyma tissues, whereas Station III had a denser cortex and no visible aerenchyma. These differences indicate that rengas roots exhibit adaptive characteristics in response to variations in flooding conditions within riparian habitats.